The relationship between emotional intelligence, social physique anxiety and life satisfaction in physical education and sports students - KARAGÖZOĞLU, CENGİZ (My University, 2013)
This study aims to retrieve the relationship between emotional intelligence, social physique anxiety and life satisfaction among physical education students whom engaged to all kinds of sport activities and a physically active population. 141 students, 89 male (%63.1) and 52 female (%36.9), average age=21.6 participated to the study and completed Schutte Emotional Intelligence Scale, Social Physique Anxiety Scale (SPAS) and The Satisfaction With Life Scale. Students with high appraisal of emotions score have lower life satisfaction. Students with high social physique anxiety (SPA) have high positive emotional intelligence (EI) total score and appraisal of emotions score but negative correlation found with life satisfaction score and SPA. Results show that gender doesn’t have a direct effect on SPA, a Univariate ANOVA conducted to reveal the difference between gender group, EI group and SPA. According to results, gender & EI has an important effect on SPA. Female students with high EI level have a higher SPA than lower EI group of both males and females.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Beden Eğitimi ve Spor; Diğer; Social Sciences and Humanities; Education; Physical Education and Sports; Other; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Emotional intelligence; social physique anxiety; life satisfaction; physical education student